A New Record From East Malaysia: Sphaerolaimus macrocirculus (Nematoda) - Rosli, Norliana Mohd; Mohd Long, Shabdin; Cheng, Cheng-Ann (Borneo Journal of Resource Science and Technology, 2016)
A new record of Sphaerolaimus macrocirculus (Filipjev 1918) in East Malaysian coastal water was described. The species was isolated from the muddy area of Muara Tebas, Sarawak, Malaysia. A total of 47 species of Sphaerolaimus have been reported worldwide. Samples of Sphaerolaimus macrocirculus were previously recorded in the sublittoral mud area of temperate country. S. macrocirculus possesses a stout body (1.1 – 1.6 mm; De Man ratios: a (body length/body width) = 16.8 – 27.5; b (body length/oesophagus length) = 2.3 – 4.3; c (body length/tail length) = 5.6 – 8.6). The circular amphid is very clear and situated at the base of the cephalic capsule. In male, the amphid ranged from 11.3 – 14.3 μm in diameter (mean = 12.7 ± 1.3) and 0.4 c.d. (corresponding diameter). In female, the amphid ranged from 7.2 – 9.4 μm in diameter (mean 7.8 ± 0.9) and 0.2 c.d. The species is characterised by the presence of eight groups of subcephalic setae at the head region and three longer terminal setae.